'Adopting place': how an entrepreneurial sense of belonging can help revitalise communities. Issue 3 (15th March 2022) - Redhead, George; Bika, Zografia
ABSTRACT: This study considers the differentiated ways in which entrepreneurs may embed themselves within place to better understand the nature of embeddedness and the processes behind both intended and unintended entrepreneurial outcomes. Whilst research has long shown that embeddedness can enable and/or constrain entrepreneurial activities, the microlevel processes behind such activities are often unacknowledged, lacking details of how, why and when embedded social values relate and integrate with enterprise in various places, thus advancing a somewhat static, one-dimensional conceptual understanding. This study attempts to broaden the understanding of embeddedness by engaging in context-sensitive theorizing from the findings of a qualitative case study in Great Yarmouth, a depleted town on the coast of East Anglia, England. Through introducing the notion of 'adopting place', we delve deeper into what it means to be spatially (dis)embedded, how this reflects a much more complex and dynamic understanding of embeddedness, and how such embeddedness can instigate change and regional development (or lack thereof), progressing a reconceptualization of place itself